Education with Ecological Roots - José Alberto Rubí-Barquero (Universidad Nacional, Costa Rica, 2012)
This paper explains how modernity develops its own form of education to achieve its objective of conquering nature, and the related environmental consequences.  In this context, this paper proposes a new education nurtured from ecological knowledge, leaving behind the fragmentary and mechanic mission of the world -a characteristic of modernity- to promote an alternative awareness focused on a new way of relationships with our natural environment and other individuals.